Molecular regulation of brain metabolism underlying circadian epilepsy. Issue Volume 62:Issue S1(2021)Supplement (4th January 2021) - Chan, Felix; Liu, Judy
Abstract: Extensive study has demonstrated that epilepsy occurs with greater frequency at certain times in the 24‐h cycle. Although these findings implicate an overlap between the circadian rhythm and epilepsy, the molecular and cellular mechanisms underlying this circadian regulation are poorly understood. Because the 24‐h rhythm is generated by the circadian molecular system, it is not surprising that this system comprised of many circadian genes is implicated in epilepsy. We summarized evidence in the literature implicating various circadian genes such as Clock, Bmal1, Per1, Rev‐erb ⍺, and Ror ⍺ in epilepsy. In various animal models of epilepsy, the circadian oscillation and the steady‐state level of these genes are disrupted. The downstream pathway of these genes involves a large number of metabolic pathways associated with epilepsy. These pathways include pyridoxal metabolism, the mammalian target of rapamycin pathway, and the regulation of redox state. We propose that disruption of these metabolic pathways could mediate the circadian regulation of epilepsy. A greater understanding of the cellular and molecular mechanism of circadian regulation of epilepsy would enable us to precisely target the circadian disruption in epilepsy for a novel therapeutic approach.